Pengaruh Sistem Informasi Akuntansi, Kompetensi Sumber Daya Manusia dan Pengendalian Intern terhadap Kualitas Laporan Keuangan - Amil Setiawati; Anwar Hariyono (Jurnal Riset Akuntansi, 2025)
This study aims to assess the influence of Accounting Information Systems, human resource (HR) competency, and internal control on the quality of financial reports at PT Semen Indonesia Logistik. The independent variables analyzed in this study include accounting information systems, human resource competency, and internal control, while the dependent variable is the quality of financial reports. The study used a saturated sampling method involving 30 employees as respondents. Data analysis was performed using SPSS version 25 software to test the relationship between variables through multiple linear regression tests. The results showed that Accounting Information Systems and HR competency did not have a significant effect on the quality of financial reports, while internal control had a significant positive effect on the quality of financial reports during the study period.